Long-Term Prevention of Congenital Thrombotic Thrombocytopenic Purpura in ADAMTS13 Knockout Mice by Sleeping Beauty Transposon-Mediated Gene Therapy. Issue 5 (May 2017) - Verhenne, Sebastien; Vandeputte, Nele; Pareyn, Inge; Izsvák, Zsuzsanna; Rottensteiner, Hanspeter; Deckmyn, Hans; De Meyer, Simon F.; Vanhoorelbeke, Karen
Abstract : Objective—: Severe deficiency in the von Willebrand factor–cleaving protease ADAMTS13 (a disintegrin and metalloproteinase with thrombospondin type 1 motif, member 13) because of mutations in the ADAMTS13 gene can lead to acute episodes of congenital thrombotic thrombocytopenic purpura (TTP), requiring prompt treatment. Current treatment consists of therapeutic or prophylactic infusions of fresh frozen plasma. However, lifelong treatment with plasma products is a stressful therapy for TTP patients. Here, we describe the use of the nonviral sleeping beauty (SB) transposon system as a gene therapeutic approach to realize lifelong expression of ADAMTS13 and subsequent protection against congenital TTP. Approach and Results—: We demonstrated that hydrodynamic tail vein injection of the SB100X system expressing murine ADAMTS13 in Adamts13 −/− mice resulted in long-term expression of supraphysiological levels of transgene ADAMTS13 over a period of 25 weeks. Stably expressed ADAMTS13 efficiently removed the prothrombotic ultralarge von Willebrand factor multimers present in the circulation of Adamts13 −/− mice. Moreover, mice stably expressing ADAMTS13 were protected against TTP. The treated mice did not develop severe thrombocytopenia or did organ damage occur when triggered with recombinant von Willebrand factor, and this up to 20 weeks after gene transfer. Conclusions—: These data demonstrate the feasibility of using SB100X-mediated gene therapy to achieve sustained expression of transgene ADAMTS13 and long-term prophylaxis against TTP in Adamts13 −/− mice. Abstract : Supplemental Digital Content is available in the text.